Natural Polymer of Iraqi Apricot Tree Gum as a Novel Corrosion Inhibitor for Mild Steel in 1 M HCl Solution - I. M. Alwaan; Fouad Kadhim Mahdi (International Journal of Chemical Engineering)
Corrosion inhibition of mild steel in 1 M hydrochloric acid using Iraqi apricot tree gum Arabic as natural polymer was studied. The weight loss method was used to predict the efficiency of the inhibitor on corrosion of mild steel in a temperature range of 17–40°C. The FTIR result of natural polymer revealed that the C=O and O-H groups were found in the structure of the natural polymer. The results of weight loss method showed that the inhibition efficiency (I%) increased with the increase in both the natural polymer concentration and the temperature; therefore, chemical adsorption mechanism was suggested in this system. The different mathematical models of the adsorption isotherms were studied and the results revealed that natural polymer was found to obey Temkin, Langmuir, and Freundlich adsorption isotherm. The activation energy of adsorption, enthalpy of adsorption, and entropy of adsorption were obtained for different concentrations of natural polymer (0, 0.1, 0.2, and 0.3 g/L) and the results showed that the thermodynamic properties decreased with the loading of a natural polymer. Gibbs free energy of adsorption results was a minus value that led to the conclusion of the spontaneous adsorption of the natural polymer in this system.